Resilience and Adaptation Strategies of Coastal Fishing Communities Under Climate Variability - Nuryati Salama; Ibnu Phonna Nurdin (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to identify the forms of climate variability and the adaptation strategies employed by fishing communities to sustain their livelihoods. The primary focus of the research is the fishing community in Gampong Alue Deah Teungoh, located in the Meraxa sub-district of Banda Aceh City, a coastal village predominantly inhabited by fisherfolk. A qualitative case study approach was used to explore this issue in depth. Findings reveal that the fishing community in Gampong Alue Deah Teungoh has developed a range of adaptation strategies in response to climate variability affecting their livelihood systems. These strategies are interpreted through Scoones’ Livelihood Framework, which includes livelihood engineering such as intensification and extensification (e.g., optimizing and expanding fishing crews), livelihood diversification (engaging in multiple income-generating activities), and spatial strategies (e.g., migration). Major climate-related challenges identified include changing rainfall patterns, high waves, coastal flooding, and unpredictable fishing seasons. These climate stressors have led to reduced fish catch and damage to coastal settlements. In response, the community has adopted sustainable coping mechanisms, such as aquaculture, coastal tourism initiatives, and the utilization of both economic and social assets. Environmentally friendly natural resource management, skills enhancement, and support from social networks also play significant roles in strengthening their resilience to climate change.